Food for memories and culture – A content analysis study of food specialties and souvenirs. (March 2015) - Lin, Lin; Mao, Pei-Chuan
Abstract: Tourist shopping and souvenirs have contributed significantly to tourism retailing and may represent the best and easiest way to experience local culture. The aim of this research is to analyze the attributes of successful food specialties and provide suggestions for the development of food souvenirs. This research initially explored the relationship among the major dimensions of souvenirs in existing literature, the critical attributes of award winning food specialties and the connections with requirements for food specialty souvenirs. A content analysis research approach was adopted in the current study. Research samples were selected from a professional food specialty institution (National Association for the Specialty Food Trade, NASFT). The 192 Gold Award winners analyzed were based on competitions from 2008 to 2013. The content analysis results indicated that the major dimensions of food specialties are the sensory, utility, and symbolic dimensions. Within these three dimensions, 15 attributes were identified. The findings of this study can provide useful information for destination marketers and hospitality businesses when developing gastronomic products and evaluating and improving existing food specialties.